2022
DOI: 10.1038/s42003-022-03548-w
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrio vulnificus stressosome is an oxygen-sensor involved in regulating iron metabolism

Abstract: Stressosomes are stress-sensing protein complexes widely conserved among bacteria. Although a role in the regulation of the general stress response is well documented in Gram-positive bacteria, the activating signals are still unclear, and little is known about the physiological function of stressosomes in the Gram-negative bacteria. Here we investigated the stressosome of the Gram-negative marine pathogen Vibrio vulnificus. We demonstrate that it senses oxygen and identified its role in modulating iron-metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…vulnificus in the environment and for survival during the infection process. For this reason, this work focused on characterization of the in vivo role of the stressosome in this marine pathogen during growth in rich media, to complement the previous studies in chemically defined minimal media [28]. This characterization confirmed that the stressosome genes are transcribed in LB+2.5 % NaCl (LBN), a rich media commonly used to culture this bacterium, and focused on the effects of the stressosome on the growth and stress response of V.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…vulnificus in the environment and for survival during the infection process. For this reason, this work focused on characterization of the in vivo role of the stressosome in this marine pathogen during growth in rich media, to complement the previous studies in chemically defined minimal media [28]. This characterization confirmed that the stressosome genes are transcribed in LB+2.5 % NaCl (LBN), a rich media commonly used to culture this bacterium, and focused on the effects of the stressosome on the growth and stress response of V.…”
Section: Introductionmentioning
confidence: 66%
“…We confirmed that there were no growth differences between the ΔRSTX mutant and the wild-type in the absence of stress, as expected, and focused on the effects of hypoxia and high temperature stresses on growth. Differences between the two strains did not emerge and the effects of hypoxia and high temperature were comparable between the two strains, despite the hypothesized role of the stressosome as an oxygen sensor [28], thus highlighting the media-specific role of the stressosome in V. vulnificus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two‐component system within che2 comprises a serine phosphatase response regulator (RsbU) and an anti‐anti‐sigma factor (RsbV) (Figure 1b ). In various Vibrio species, these are involved in O 2 ‐dependent stress responses and in regulating iron metabolism (Heinz et al, 2022 ; Jia et al, 2016 ). We investigated potential interactions between the CheA2 histidine kinase and the RsbU response regulator using a bacterial two‐hybrid assay, but observed no CheA2‐RsbU interactions (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The same holds true for the edge between V. vulnificus quantity and O 2 mean 0–0 , which has been observed elsewhere [ 65 , 66 , 67 ]. While changes in oxygen saturation can affect the metabolism of V. vulnificus [ 68 ], this edge more likely reflects the strong effects of temperature on oxygen solubility.…”
Section: Discussionmentioning
confidence: 99%